2010
DOI: 10.1074/jbc.m109.087122
|View full text |Cite
|
Sign up to set email alerts
|

CYR61 Regulates BMP-2-dependent Osteoblast Differentiation through the αvβ3 Integrin/Integrin-linked Kinase/ERK Pathway

Abstract: Osteoporosis is one of the most common bone pathologies. A number of novel molecules have been reported to increase bone formation including cysteine-rich protein 61 (CYR61), a ligand of integrin receptor, but mechanisms remain unclear. It is known that bone morphogenetic proteins (BMPs), especially BMP-2, are crucial regulators of osteogenesis. However, the interaction between CYR61 and BMP-2 is unclear. We found that CYR61 significantly increases proliferation and osteoblastic differentiation in MC3T3-E1 ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 64 publications
(51 reference statements)
6
90
2
Order By: Relevance
“…Additionally, as mentioned previously, AKT was a linker between ILK and NF-κB. Early reports showed that ILK could regulate the ERK pathway as well, but until the recent study, the interaction manner were still not quite clear (Su et al, 2010). The WB results showed that the phosphorylation of AKT and ERK were attenuated by ILK silencing ( Figure 6A).…”
Section: The Ilk Silencing Downreagulated the Phosphorylation Of Akt mentioning
confidence: 62%
“…Additionally, as mentioned previously, AKT was a linker between ILK and NF-κB. Early reports showed that ILK could regulate the ERK pathway as well, but until the recent study, the interaction manner were still not quite clear (Su et al, 2010). The WB results showed that the phosphorylation of AKT and ERK were attenuated by ILK silencing ( Figure 6A).…”
Section: The Ilk Silencing Downreagulated the Phosphorylation Of Akt mentioning
confidence: 62%
“…Cyr61 was shown to activate small GTPase Rac1 in prostate cancer cells (55), which is a widely accepted activator of dendritic growth (3,56,57). Cyr61 can also act upstream of PI3K-mTOR and ERK signaling pathways (58,59), raising the intriguing possibility that the initial activation of cyr61 expression downstream of these kinases is an early step in a positive feedback loop that potentiates their progrowth effects and coordinates the actions of these kinases with remodeling of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…However, the following five proteins were identified as being significantly regulated in the presence of HA or CS1: (i) CCN1 and THBS2 were up-regulated in the presence of CS1 (FC ϭ 0.8 and 0.6 compared with the untreated control). As discussed earlier, both proteins are involved in cell adhesion and, moreover, osteoblast differentiation either directly by increasing the BMP synthesis (62) or indirectly by the activation of TGF-␤ (54). (ii) POSTN, the Pentraxin-related protein 3 (PTX3), and the FTH1 were significantly down-regulated in the presence of HA (FC ϭ Ϫ0.9, Ϫ1.3, and Ϫ1.6 compared with the untreated control).…”
Section: Influence Of Various Gags On the Matrix Vesicle Proteomementioning
confidence: 99%
“…Moreover, in comparative analysis to CS1, the growth factor CCN2 was identified to be up-regulated by sHA1 (FC ϭ 2.6). Both CCN family members were shown to induce the osteoblastogenesis (62)(63)(64).…”
Section: Influence Of Various Gags On the Matrix Vesicle Proteomementioning
confidence: 99%